IS FORAGING BEHAVIOR A DAILY ACTIVITY IN Hemidactylus platyurus? - Huda Wiradarma; Auni Ade Putri; Tri Heru Widarto (Masyarakat Zoologi Indonesia, 2021)
To understand the role of the flat-tailed gecko on pest control in urbanized areas, we observed the foraging behavior and daily activity of H. platyurus. It is one of the house geckos easily found but more studies on their behavior are still lacking. The observation was conducted between 14−27 May 2021, for 18 hours starting from 09.00 to 03.00 WIB using the ad libitum sampling method. Our result suggests that the foraging behavior was found almost every hour of observation, which is strongly influenced by relative humidity and insect abundance. This gecko was observed as a sit-and-wait predator or passively searching for prey. Our observation also indicated that this species has potential to control one of the household pests, the adult ants (alates). Hopefully, this study contributed to the understanding of the foraging behavior of the flat-tailed gecko. However, more studies are needed for better understanding of foraging behavior in the flat-tailed gecko.Keywords: foraging, daily activity, Hemidactylus platyurus.